Drosophila Hephaestus/polypyrimidine tract binding protein is required for dorso-ventral patterning and regulation of signalling between the germline and soma. - Suzanne M McDermott; Ilan Davis (PLoS ONE)
In the Drosophila oocyte, gurken (grk) mRNA encodes a secreted TGF-α signal that specifies the future embryonic dorso-ventral axes by altering the fate of the surrounding epithelial follicle cells. We previously identified a number of RNA binding proteins that associate specifically with the 64 nucleotide grk localization signal, including the Drosophila orthologue of polypyrimidine tract-binding protein (PTB), Hephaestus (Heph). To test whether Heph is required for correct grk mRNA or protein function, we used immunoprecipitation to validate the association of Heph with grk mRNA and characterized the heph mutant phenotype. We found that Heph is a component of grk mRNP complexes but heph germline clones show that Heph is not required for grk mRNA localization. Instead, we identify a novel function for Heph in the germline and show that it is required for proper Grk protein localization. Furthermore, we show that Heph is required in the oocyte for the correct organization of the actin cytoskeleton and dorsal appendage morphogenesis. Our results highlight a requirement for an mRNA binding protein in the localization of Grk protein, which is independent of mRNA localization, and we propose that Heph is required in the germline for efficient Grk signalling to the somatic follicle cells during dorso-ventral patterning.